Role of Psychology Treatment in "Anxiety Disorder" - Dr. Mahesh Kumar Gajurel, (Journal of Balkumari College, 2022)
In order to manage the emotional and psychological problems in special population such as mental retardation. HIV positive cases and so on. A comprehensive management of this type of cases includes psychotherapy. Here it is necessary to know about this concept and its beauty in various disorders. It is a psychological method which is called psychotherapy (Talking Cure). Psychotherapy is a systematic attempt to manage the mental and emotional disorders with the help of psychological means a variant of this approach came in 1960s. Which was called cognitive behavior therapy. Recent days this approached has been brought revolution in management of psychological, behavioral and emotional problems. This paper will enhance our knowledge regarding status of psychological method in various disorders and mental illnesses.